Utility of Adrenal Vein Sampling to Guide Surgical Management of Hypercortisolism - Brandon Tran; James Y. Lim; Brian Park (Case Reports in Endocrinology)
We report a case of successfully lateralized adrenal cortisol hypersecretion by adrenal venous sampling (AVS) and improved by surgery. AVS is a commonly used tool to guide surgical management of primary hyperaldosteronism. It can determine lateralization, leading to unilateral adrenalectomies of the correct side, or nonlateralization, which precludes surgery. The use of AVS in determining lateralization in hypercortisolism is a growing field of discussion. Currently, there is no defined or unanimous protocol behind procedural details and interpretation of results. In this report, we describe the AVS protocol at our institution for hypercortisolism, interpretation of the results, and corresponding surgical outcomes for a case of mild autonomous cortisol secretion.